EFEKTIVITAS PROGRAM KAMPUNG KB (KELUARGA BERKUALITAS) LESTARI UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM BER KB (KELUARGA BERENCANA) DI DESA TRIWARNO KECAMATAN BANYUURIP KABUPATEN PURWOREJO - Ratri Januar, Dhiya; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2024)
Effectiveness of a program refers to the extent to which a program successfully achieves its intended goals and outcomes. Kampung Keluarga Berkualitas Lestari is one of the villages classified as having high poverty levels and low community welfare in Banyuurip District. The number of family planning acceptors in Kampung Keluarga Berkualitas Lestari is also considered to be lower compared to other Quality Family Village. This study aims to analyze the effectiveness of the Kampung Keluarga Berkualitas Lestari Program in Triwarno Village to increase community participation in family planning in Triwarno Village, Purworejo Regency, as well as its supporting and inhibiting factors. The study uses Sutrisno's program effectiveness theory. The criteria for factors that inhibit and support program effectiveness are evaluated based on environmental conditions, resources, and the characteristics and capabilities of implementing agents. The research method used is descriptive qualitative with data collection techniques including interviews and documentation or literature review. The results indicate that the understanding of the program and target accuracy in the Kampung Keluarga Berkualitas Lestari Program are not yet effective due to the lack of community participation in family planning, especially among men, and the low levels of economic and educational welfare in Triwarno Village, while timeliness and tangible changes are already functioning well. Recommendations include enhancing education and counseling on the benefits of family planning and providing clear information on the various available family planning methods, both short-term and long-term, to achieve the effectiveness of Kampung Keluarga Berkualitas Lestari.